OPN Polymorphism Is Related to the Chemotherapy Response and Prognosis in Advanced NSCLC. (5th August 2014) - Hao, Yanzhang; Liu, Jianwei; Wang, Ping; Wang, Feng; Yu, Zeshun; Li, Mianli; Chen, Shaoshui; Ning, Fangling
Abstract : Background. Osteopontin (OPN) is associated with prognosis of patients with non-small-cell lung cancer (NSCLC). However, little is known about the association between OPN gene polymorphism and the chemotherapy response in NSCLC patients. Methods. A total of 497 patients with inoperable advanced stage of NSCLC (stages III B and IV NSCLC) were enrolled. All patients had received platinum-based chemotherapy. OPN gene polymorphisms at 156 GG/G, 443 C/T, and −66T/G were determined. Results. The genotypes and allele frequency of −443C>T were significantly different between the responders and nonresponders. Responders had a markedly higher frequency of −443TT genotype than responders (40.71% versus 19.09%, P < 0.001 ). With CC as reference, the TT genotype carriers had a higher chance to be well responders (adjusted OR = 4.43, 95% CI: 2.60–7.53, adjusted P < 0.001 ). The median overall survival time for patients with −443CC, −443CT, and −443TT genotype carriers was significantly different. Multivariate Cox proportional hazards regression models showed that OPN −443C>T gene polymorphisms were closely correlated to poor NSCLC prognosis. Conclusion. OPN −443C>T gene polymorphism may be used as a molecular marker to predict the treatment response to chemotherapy in advanced NSCLC patients.